Bakthin and the philosophy of the act in research and teaching: An Academic Experience at the Federal University of Pernambuco (Brazil) - Sampaio, Maria Cristina (Revista Conexão Letras, 2016)
The subject matter of this paper was inspired in our experience in research and teaching on the Postgraduate Linguistics and Arts Program at the Federal University of Pernambuco, in Brazil’s Northeastern region between 2007 and 2015, which led to the publication of papers, academic magazine articles, chapters in books, research projects, dissertations and theses. To that end the intention is to analyze to what extent the study of Bajtin’s (1997a) work, Towards a philosophy of the ethical act , written between 1920 and 24, seen from the different philosophical traditions (phenomenology, ontology, metaphysics and hermeneutics) in the Philosophy of Language subject of the Postgraduate Arts Program, offered a fruitful dialog between research and teaching, benefi ting the manner in which young people at the research initiation level as well as Masters and Doctorate candidates approach subjectivity in their own academic studies, and the consequences of inaugurating a new place for ethical and philosophical observation for language research and teaching.